SOIL AND WATER MICROORGANISM DIVERSITY OF MANGROVE FOREST OF TELUK KELUMPANG, SELAT LAUT AND SELAT SEBUKU NATURAL RESERVE - Halwany, Wawan; Andriani, Susy (Indonesian Journal of Forestry Research, 2015)
Mangrove is a unique ecosystem that has complex biotic and abiotic components. Soil and water microorganisms have function as decomposer in mangrove forest ecosystem. This paper studies the soil and water microorganisms' diversity, their potential, function in ecosystem and their role as environmental parameters in mangrove area of Teluk Kelumpang, Selat Laut and Selat Sebuku Natural Reserve (Kelautku Natural Reserve). Data of soil and water microorganisms were recorded from soil and water samplings then analyzed in the laboratory. Results show that benthos in Selat Sebuku figure the highest diversity index. Anadara granosa is one of the common benthos found in Selat Sebuku. In contrary the phytoplankton in Selat Sebuku is the lowest value compared to the other two locations, due to the settlements in the locations and it was suspected that Selat Sebuku has a relatively larger wave exposure than the two other locations. In addition, input of organic matters from the settlements in Teluk Kelumpang and Selat Laut is also effected by the growth of phytoplankton. Cyanophyta found in Teluk Kelumpang and Selat Laut was genera of Oscillatoria that showed high tolerance genera to the environment conditions.